Anfidinolidos isolados de Stragulum bicolor (van Ofwegen & Haddad) e sesquiterpenos de Ophionereis reticulata (Say), dois invertebrados marinhos endêmicos do litoral brasileiro - Gomes, Bruno de Araújo (2017)
The goal of the present work was to investigate the organic extracts of the marine species Stragulum bicolor (Octocorallia: Clavulariidae) and Ophionereis reticulata (Ofiura: Ophionereididae), two endemic invertebrates of the Brasilian seas, widespread in the coast of Ceara State. The methanolic extract of S. Bicolor was subjected to successive chromatography columns on silica gel to yield two amphidinolides, the amphidinolide P (SB 2H) and its methy ester derivative, 3-O-methyl amphidinolide P (SB 2F), which is described for the first time. Posteriorly, using high performance liquid cromatography (HPLC), was isolated four amphidinolides, three of which are new, and the known amphidinolide T (SB 5E). The new compounds were designated as amphidinolides B8 (SB 4E), B9 (SB 4D) and C4 (SB 4M). From the methanolic extract of O. Reticulata, using chromatography on silica gel and Sephadex LH-20, were isolated three sesquiterpenes of skeleton chamigrane: elatol (OREDM2F), isoobtusadiene (OREDM2D) and acetyl-isoobtusadiene (OREDM2B). All compounds isolated from S. bicolor were assayed against the cancer cell line HCT-116 (colon) showing weak or moderate activities. The structures of all compounds were determinated by means of spectroscopic tecniques (1H and 13C NMR – 1D and 2D) and HRESIMS.